Investigación del patrimonio cultural gastronómico de la fiesta del Inti Raymi en la localidad de Cayambe - Torres Delgado, Karen Yessenia (2018)
The canton Cayambe is located approximately 1 hour and 30 minutes from the city of Quito is a place full of history and traditions, has beautiful scenery and its people are very friendly, in the months of June and July are celebrated the feasts of San Pedro and sun the same as a fusion of Catholic religious festivals with indigenous festivals in honor of the god Inti or sun, these festivities have their cuisine so the need was born to create this research to make an analysis of culture and Inti Raymi gastronomy in the town of Cayambe. This investigation tried to realize a gastronomic inventory of the preparations that are made during the festivity, beginning with a survey of information through the quantitative method of the research methodology, after obtaining this information a field investigation was made and the information was collected through interviews with experts and gastronomic managers to finalize with the elaboration of a gastronomic inventory of the typical Inti Raymi dishes.